Nigeria : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2018)
This Selected Issues paper analyzes mobilization of tax revenues in Nigeria. Low non-oil revenue mobilization is affecting the government's objectives to expand growth-enhancing expenditure priorities, foster higher growth, and comply with its fiscal rule which limits the federal government deficit to no more than 3 percent of GDP. There is significant revenue potential from structural tax measures. A broad-based and comprehensive tax reform program is needed in the short and medium term to address these objectives and generate sustainable revenue growth by broadening the bases of income and consumption taxes, closing loopholes and leakage created by corporate tax holidays and the widespread use of other associated tax expenditures, as well as creating incentives for the subnational tiers of government to raise their own source revenues.